Learning Empathy Through Virtual Reality: Multiple Strategies for Training Empathy-Related Abilities Using Body Ownership Illusions in Embodied Virtual Reality - Bertrand, Philippe; Guegan, Jérôme; Robieux, Léonore; McCall, Cade Andrew; Zenasni, Franck (Frontiers in Robotics and AI, 2018)
Several disciplines have investigated the interconnected empathic abilities behind the proverb “to walk a mile in someone else’s shoes” to determine how the presence, and absence, of empathy-related phenomena affect prosocial behavior and intergroup relations. Empathy enables us to learn from others’ pain and to know when to offer support. Similarly, virtual reality (VR) appears to allow individuals to step into someone else’s shoes, through a perceptual illusion called embodiment, or the body ownership illusion. Considering these perspectives, we propose a theoretical analysis of different mechanisms of empathic practices in order to define a possible framework for the design of empathic training in VR. This is not intended to be an extensive review of all types of practices, but an exploration of empathy and empathy-related phenomena. Empathy-related training practices are analyzed and categorized. We also identify different variables used by pioneer studies in VR to promote empathy-related responses. Finally, we propose strategies for using embodied VR technology to train specific empathy-related abilities.